Impact of the COVID-19 pandemic on non-COVID-19 community-acquired pneumonia: a retrospective cohort study - Keith R Walley; Andre Kalil; Terry Lee; Kelly A Cawcutt; John H Boyd; James A Russell (BMJ Open Respiratory Research)
Background The COVID-19 pandemic could impact frequency and mortality of non-COVID-19 community-acquired pneumonia (CAP). Changes in frequency, patient mix, treatment and organ dysfunction could cascade together to increase mortality of CAP during compared with pre-COVID-19.Methods Hospitalised CAP patients at St. Paul’s Hospital, Vancouver, Canada pre-COVID-19 (fiscal years 2018/2019 and 2019/2020) and during COVID-19 pandemic (2020/2021 and 2021/2022) were evaluated.Results In 5219 CAP patients, there was no significant difference prepandemic versus during pandemic in mean age, gender and Charlson Comorbidity Score. However, hospital mortality increased significantly from pre-COVID-19 versus during COVID-19 (7.5% vs 12.1% respectively, (95% CI for difference: 3.0% to 6.3%), p<0.001), a 61% relative increase, coincident with increases in ICU admission (18.3% vs 25.5%, respectively, (95% CI for difference: 5.0% to 9.5%) p<0.001, 39% relative increase) and ventilation (12.7% vs 17.5%, respectively, (95% CI for difference: 2.8% to 6.7%) p<0.001, 38% relative increase). Results remained the same after regression adjustment for age, sex and Charlson score. CAP hospital admissions decreased 27% from pre-COVID-19 (n=1349 and 1433, 2018/2019 and 2019/2020, respectively) versus the first COVID-19 pandemic year (n=1047 in 2020/2021) then rose to prepandemic number (n=1390 in 2021/2022). During prepandemic years, CAP admissions peaked in winter; during COVID-19, the CAP admissions peaked every 6 months.Conclusions and relevance This is the first study to show that the COVID-19 pandemic was associated with increases in hospital mortality, ICU admission and invasive mechanical ventilation rates of non-COVID-19 CAP and a transient, 1-year frequency decrease. There was no winter seasonality of CAP during the COVID-19 pandemic era. These novel findings could be used to guide future pandemic planning for CAP hospital care.